2011
DOI: 10.4314/ijbcs.v5i2.72133
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of aviation fuel by microorganisms isolated from tropical polluted soils

Abstract: The degradation of aviation fuel was observed in soil samples from a polluted site at the aviation fuel depot, Lagos Airport, Nigeria. The percentage of occurrence of bacterial aviation fuel-utilizers were less than 1.0% of the heterotrophic populations, while the fungal-degraders were between 2.547-16.053%. There were no significant statistical differences for both the bacteria and fungi estimations among the soil samples. Enrichment of soil samples with aviation fuel resulted in the isolation of five bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…[28], which proved that the existence of microorganism is also dependent of the level of TOC as one of the major source of nutrient. Table: 2 showed that the bacterial load was high for all samples, this may be because the crude oil contaminated soil favored the growth of the organisms present in the soil sample, similar results were seen in the research conducted by Omotayo et al [27]. The water holding capacity ranged from 22.4 -32.0% the high value obtained was because of the high organic matter content, which is considered integral in the capacity of a soil to maximize water storage through its effect on creating and stabilizing soil pores and its absorption capacity.…”
Section: Discussionsupporting
confidence: 82%
“…[28], which proved that the existence of microorganism is also dependent of the level of TOC as one of the major source of nutrient. Table: 2 showed that the bacterial load was high for all samples, this may be because the crude oil contaminated soil favored the growth of the organisms present in the soil sample, similar results were seen in the research conducted by Omotayo et al [27]. The water holding capacity ranged from 22.4 -32.0% the high value obtained was because of the high organic matter content, which is considered integral in the capacity of a soil to maximize water storage through its effect on creating and stabilizing soil pores and its absorption capacity.…”
Section: Discussionsupporting
confidence: 82%
“…However, Rhodotorula strains were isolated from oil-and petroleum-polluted environments and as contaminants in stored products (Gaylarde et al, 1999;Yemashova et al, 2007) or have been described as being able to degrade oil compounds, with a preference for the saturated fractions represented by the aliphatic hydrocarbons and higher alkanes (Shailubhai et al, 1984;White et al, 1987;van Beilen et al, 2003;Omotayo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Chikere and Ekwuabu [22] carried out the culture-dependent characterization of hydrocarbon utilizing bacteria in the selected crude-oil impacted sites in Bodo, Ogoniland, Nigeria and reported the presence of Micrococcus luteus, Pseudomonas aeruginosa, Proteus vulgaris and Serratia marcescens which utilized hydrocarbons. Omotayo et al [23] in their work on the degradation of aviation fuel by microorganisms isolated from tropical polluted soils and Yakubu [19] in their work on the biodegradation of Lagoma crude oil using pig dung isolated similar organisms and reported that they had petroleum hydrocarbon-degrading potentials.…”
Section: Discussionmentioning
confidence: 99%
“…Chikere and Azubike [25] in their work on the characterization of hydrocarbon-utilizing fungi from hydrocarbon polluted sediments and water isolated Aspergillus, Penicillium, Cladosporium and Candida. Omotayo et al [23] also isolated Candida tropicalis from tropical polluted soils and reported that it degraded aviation fuel while Candida spp. have been reported by Amund and Nwokoye [26] [30] studied the bacterial degradation of crude oil by gravimetric analysis and reported that bacteria contribute largely in the degradation of hydrocarbons and its compounds.…”
Section: Discussionmentioning
confidence: 99%